Apelin Compared With Dobutamine Exerts Cardioprotection and Extends Survival in a Rat Model of Endotoxin-Induced Myocardial Dysfunction*. Issue 4 (April 2017) - Chagnon, Frederic; Coquerel, David; Salvail, Dany; Marsault, Eric; Dumaine, Robert; Auger-Messier, Mannix; Sarret, Philippe; Lesur, Olivier
Abstract : Objective: Dobutamine is the currently recommended β-adrenergic inotropic drug for supporting sepsis-induced myocardial dysfunction when cardiac output index remains low after preload correction. Better and safer therapies are nonetheless mandatory because responsiveness to dobutamine is limited with numerous side effects. Apelin-13 is a powerful inotropic candidate that could be considered as an alternative noncatecholaminergic support in the setting of inflammatory cardiovascular dysfunction. Design: Interventional controlled experimental animal study. Setting: Tertiary care university-based research institute. Subjects: One hundred ninety-eight adult male rats. Interventions: Using a rat model of "systemic inflammation–induced cardiac dysfunction" induced by intraperitoneal lipopolysaccharide injection (10 mg/kg), hemodynamic efficacy, cardioprotection, and biomechanics were assessed under IV osmotic pump infusions of apelin-13 (0.25 μg/kg/min) or dobutamine (7.5 μg/kg/min). Measurements and Main Results: In this model and in both in vivo and ex vivo studies, apelin-13 compared with dobutamine provoked distinctive effects on cardiac function: 1) optimized cardiac energy–dependent workload with improved cardiac index and lower vascular resistance, 2) upgraded hearts' apelinergic responsiveness, and 3) consecutive downstream advantages, including increased urine output, enhanced plasma volume, reduced weight loss, and substantially improved overall outcomes. In vitro studies confirmed that these apelin-13–driven processes encompassed a significant and rapid reduction in systemic cytokine release with dampening of myocardial inflammation, injury, and apoptosis and resolution of associated molecular pathways. Conclusions: In this inflammatory cardiovascular dysfunction, apelin-13 infusion delivers distinct and optimized hemodynamic support (including positive fluid balance), along with cardioprotective effects, modulation of circulatory inflammation and extended survival. Abstract : Supplemental Digital Content is available in the text.